Direct injection molding and mechanical properties of high strength steel/composite hybrids. (15th February 2019) - Zhang, Yiben; Sun, Lingyu; Li, Lijun; Huang, Bincheng; Wang, Taikun; Wang, Yantao
Abstract: Metal polymer hybrid technology is a promising way of automotive weight reduction and safety improvement. In this study, high strength steel and glass-fiber reinforced PA66 composite were integrated by direct injection molding process. The mechanical properties and failure behavior of steel/composite hybrids under tension, bending, mode I and II fracture loads were investigated experimentally, theoretically and numerically. The properties of the interface between steel and composite were measured using double cantilever beam and end-notched flexure tests for the first time. The analytical model and finite element simulation considering the interface mechanical behavior were proposed and validated. They can be utilized to predict the mechanical properties and progressive failure process of hybrid material cost-effectively and accurately. It is found that the cracks initiate at the interface, and then propagate through composite until the hybrid material loses load-carrying capacity completely. The steel dominates the load-bearing capacity, and the interface dominates the failure process. The results obtained in this study offer a scientific guidance and theoretical basis for the engineering application of metal polymer hybrid materials.